2020
DOI: 10.1093/cid/ciaa1225
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) Asymptomatic Infections in 2 Large Academic Health Systems in Wisconsin

Abstract: SARS-CoV-2 asymptomatic infections may play a critical role in disease transmission. We aim to determine the prevalence of asymptomatic SARS-CoV-2 infection at two hospital systems in two counties in Wisconsin. The SARS-CoV-2 prevalence was 1% or lower at both systems despite the higher incidence of COVID-19 in Milwaukee county

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 3 publications
0
5
0
1
Order By: Relevance
“…First, we could not follow up whether the asymptomatic cases subsequently developed the disease or not. Reports suggested that most asymptomatic cases did not onset, although the onset rates were different in each study [ 21 , 22 ]. Moreover, the viral load may fluctuate before and after the onset of the disease [ 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…First, we could not follow up whether the asymptomatic cases subsequently developed the disease or not. Reports suggested that most asymptomatic cases did not onset, although the onset rates were different in each study [ 21 , 22 ]. Moreover, the viral load may fluctuate before and after the onset of the disease [ 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Appare però evidente che, nella valutazione della probabilità pre-test di malattia nei bambini con patologia acuta, il giudizio clinico del pediatra dovrà essere affiancato dalla valutazione del quadro epidemiologico (prevalenza del virus nella popolazione, valutazione della situazione sanitaria dei contatti stretti). In generale, per quanto riguarda il tracciamento del virus nella popolazione pediatrica, oltre alle difficoltà evidenziate in questo studio relative all'individuazione di quadri clinici suggestivi di infezione da SARS-CoV-2 tra i bambini con malattie acute, vanno considerate quelle legate all'identificazione dell'infezione nei bambini asintomatici, la cui prevalenza è segnalata in un numero crescente di studi [16][17][18] . L'opportunità di uno screening nella popolazione pediatrica, e in particolare nelle scuole, rimane a oggi un problema aperto e oggetto di discussione in Sanità pubblica 19 .…”
Section: Conclusioniunclassified
“…With no end of the pandemic in sight, many reports are emerging on spread of disease by asymptomatic individuals [13,14]. Both studies with vocal activities reported in this review [15] have recorded particles sizes mostly in 5-10 µm range, which did not depend on the loudness or pitch of the vocal activity.…”
Section: Discussionmentioning
confidence: 75%